PELAKSANAAN KEWENANGAN PEMERINTAH KOTA PEKANBARU DALAM PENINGKATAN KUALITAS PERMUKIMAN KUMUH DI KECAMATAN PEKANBARU KOTA TAHUN 2017-2018 - Godang Bagus Nugraha; Rury Febrina (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
It is a problem faced by almost all major cities in Indonesia. According to the 2016 new pekanbaru city ordinance on the prevention and quality of slums, it has been arranged about the government's authority for the new aphiant in the improved quality of slums under section 5. It is still an area of poor housing and high population growth that is a question of exercising authority. The problem with this research is how the government's exercise of authority in the new pekanbaru government increases the quality of slum settlements in the new city and what factors are impeding the rise in the quality of slum settlements in the new city? The aim of the study is to reflect on the execution of authority conducted by the new PPN government on the increase of slum settlements in 2017-2018, and to reflect on factors that are impeding the performance of improving the quality of slum settlements in 2017-2018. The study USES a qualitative approach with a descriptive approach. The data-collection technique used was interviews and documenting. Data analysis is done when empirical data are acquired in a collection of words rather than a set of Numbers. The results of this study are in implementing the authority carried out by the new pekanbaru city government in 2017, the improvement program of slum settlements is ongoing, but in the exercise of its authority, there is still an overdue loss of information on how its budget is overdue. Offline land was considered to be completed by the handling of the slums, but in reality people said there was still something left to handle in 2017. And in 2018 the program is projected to be impeded due to a limited budget, so the establishment of the current location is unknown because the decree for the 2018 housing settlement is not available, the housing sector should not be established until the completion of the program. As for the retard factor in the rise in the quality of slum settlements in the new city next to budgets is population densities and the creation of illegal, undefined legal states, which slows down the process of improving the quality of slum settlements. Keywords: assign location, manage of slums, manage of slums